cat theory tweaks
[lambda.git] / advanced_topics / monads_in_category_theory.mdwn
index 0c60f2e..2467079 100644 (file)
@@ -379,89 +379,97 @@ So our **(lemma 2)** is:
 Finally, we substitute <code>((join G') -v- (M &gamma;) -v- &phi;)</code> for <code>&gamma; &lt;=&lt; &phi;</code> in the monad laws. For simplicity, I'll omit the "-v-".
 
 <pre>
-       for all &phi;,&gamma;,&rho; in T, where &phi; is a transformation from F to MF', &gamma; is a transformation from G to MG', R is a transformation from R to MR', and F'=G and G'=R:
+       For all &rho;, &gamma;, &phi; in T,
+       where &phi; is a transformation from F to MF',
+       &gamma; is a transformation from G to MG',
+       &rho; is a transformation from R to MR',
+       and F'=G and G'=R:
 
-       (i) &gamma; <=< &phi; etc are also in T
+            (i) &gamma; <=< &phi; etc are also in T
        ==>
-       (i') ((join G') (M &gamma;) &phi;) etc are also in T
+           (i') ((join G') (M &gamma;) &phi;) etc are also in T
 
 
-       (ii) (&rho; <=< &gamma;) <=< &phi;  =  &rho; <=< (&gamma; <=< &phi;)
+
+           (ii) (&rho; <=< &gamma;) <=< &phi;  =  &rho; <=< (&gamma; <=< &phi;)
        ==>
-                (&rho; <=< &gamma;) is a transformation from G to MR', so:
-                       (&rho; <=< &gamma;) <=< &phi; becomes: (join R') (M (&rho; <=< &gamma;)) &phi;
-                                                       which is: (join R') (M ((join R') (M &rho;) &gamma;)) &phi;
-                       substituting in (ii), and helping ourselves to associativity on the rhs, we get:
+                    (&rho; <=< &gamma;) is a transformation from G to MR', so
+                        (&rho; <=< &gamma;) <=< &phi; becomes: ((join R') (M (&rho; <=< &gamma;)) &phi;)
+                                                       which is: ((join R') (M ((join R') (M &rho;) &gamma;)) &phi;)
 
-            ((join R') (M ((join R') (M &rho;) &gamma;)) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
-                     ---------------------
-                       which by the distributivity of functors over composition, and helping ourselves to associativity on the lhs, yields:
-                    ------------------------
-            ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
-                                                             ---------------
-                       which by lemma 1, with &rho; a transformation from G' to MR', yields:
-                                                             -----------------
-            ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (join MR') (MM &rho;) (M &gamma;) &phi;)
+                        similarly, &rho; <=< (&gamma; <=< &phi;) is:
+                                                       ((join R') (M &rho;) ((join G') (M &gamma;) &phi;))
 
-                       which will be true for all &rho;,&gamma;,&phi; just in case:
+                        substituting these into (ii), and helping ourselves to associativity on the rhs, we get:
+                ((join R') (M ((join R') (M &rho;) &gamma;)) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
+    
+                        which by the distributivity of functors over composition, and helping ourselves to associativity on the lhs, yields:
+                ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
+  
+                        which by lemma 1, with &rho; a transformation from G' to MR', yields:
+                ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (join MR') (MM &rho;) (M &gamma;) &phi;)
 
-             ((join R') (M join R')) = ((join R') (join MR')), for any R'.
+                        which will be true for all &rho;,&gamma;,&phi; only when:
+                ((join R') (M join R')) = ((join R') (join MR')), for any R'.
 
-                       which will in turn be true just in case:
+                        which will in turn be true when:
+       (ii') (join (M join)) = (join (join M))
 
-       (ii') (join (M join)) = (join (join M))
 
 
-       (iii.1) (unit F') <=< &phi;  =  &phi;
+        (iii.1) (unit G') <=< &gamma;  =  &gamma;
+                when &gamma; is a natural transformation from some FG' to MG'
        ==>
-                       (unit F') is a transformation from F' to MF', so:
-                               (unit F') <=< &phi; becomes: (join F') (M unit F') &phi;
-                                                  which is: (join F') (M unit F') &phi;
-                               substituting in (iii.1), we get:
-                       ((join F') (M unit F') &phi;) = &phi;
-
-                       which will be true for all &phi; just in case:
+                        (unit G') is a transformation from G' to MG', so:
+                        (unit G') <=< &gamma; becomes: ((join G') (M unit G') &gamma;)
 
-                ((join F') (M unit F')) = the identity transformation, for any F'
+                        substituting in (iii.1), we get:
+                        ((join G') (M unit G') &gamma;) = &gamma;
 
-                       which will in turn be true just in case:
+                        which will be true for all &gamma; just in case:
+                ((join G') (M unit G')) = the identity transformation, for any G'
 
+                        which will in turn be true just in case:
        (iii.1') (join (M unit) = the identity transformation
 
 
-       (iii.2) &phi;  =  &phi; <=< (unit F)
-       ==>
-                       &phi; is a transformation from F to MF', so:
-                               unit <=< &phi; becomes: (join F') (M &phi;) unit
-                               substituting in (iii.2), we get:
-                       &phi; = ((join F') (M &phi;) (unit F))
-                                                  --------------
-                               which by lemma (2), yields:
-                            ------------
-                       &phi; = ((join F') ((unit MF') &phi;)
-
-                               which will be true for all &phi; just in case:
-
-               ((join F') (unit MF')) = the identity transformation, for any F'
 
-                               which will in turn be true just in case:
 
+        (iii.2) &gamma;  =  &gamma; <=< (unit G)
+                when &gamma; is a natural transformation from G to some MR'G
+       ==>
+                        unit <=< &gamma; becomes: ((join R'G) (M &gamma;) unit)
+                       
+                        substituting in (iii.2), we get:
+                        &gamma; = ((join R'G) (M &gamma;) (unit G))
+               
+                        which by lemma 2, yields:
+                        &gamma; = ((join R'G) ((unit MR'G) &gamma;)
+
+                         which will be true for all &gamma; just in case:
+                ((join R'G) (unit MR'G)) = the identity transformation, for any R'G
+
+                        which will in turn be true just in case:
        (iii.2') (join (unit M)) = the identity transformation
 </pre>
 
 
 Collecting the results, our monad laws turn out in this format to be:
 
-</pre>
-       when &phi; a transformation from F to MF', &gamma; a transformation from F' to MG', &rho; a transformation from G' to MR' all in T:
+<pre>
+       For all &rho;, &gamma;, &phi; in T,
+       where &phi; is a transformation from F to MF',
+       &gamma; is a transformation from G to MG',
+       &rho; is a transformation from R to MR',
+       and F'=G and G'=R:
 
-       (i') ((join G') (M &gamma;) &phi;) etc also in T
+           (i') ((join G') (M &gamma;) &phi;) etc also in T
 
-       (ii') (join (M join)) = (join (join M))
+          (ii') (join (M join)) = (join (join M))
 
        (iii.1') (join (M unit)) = the identity transformation
 
-       (iii.2')(join (unit M)) = the identity transformation
+       (iii.2') (join (unit M)) = the identity transformation
 </pre>